Panel 4: Recent advances in understanding the natural history of the otitis media microbiome and its response to environmental pressures. (March 2020) - Marsh, Robyn L.; Aho, Celestine; Beissbarth, Jemima; Bialasiewicz, Seweryn; Binks, Michael; Cervin, Anders; Kirkham, Lea-Ann S.; Lemon, Katherine P.; Slack, Mary P.E.; Smith-Vaughan, Heidi C.
Abstract: Objective: To perform a comprehensive review of otitis media microbiome literature published between 1 st July 2015 and 30th June 2019. Data sources: PubMed database, National Library of Medicine. Review methods: Key topics were assigned to each panel member for detailed review. Draft reviews were collated and circulated for discussion when the panel met at the 20th International Symposium on Recent Advances in Otitis Media in June 2019. The final draft was prepared with input from all panel members. Conclusions: Much has been learned about the different types of bacteria (including commensals) present in the upper respiratory microbiome, but little is known about the virome and mycobiome. A small number of studies have investigated the middle ear microbiome; however, current data are often limited by small sample sizes and methodological heterogeneity between studies. Furthermore, limited reporting of sample collection methods mean that it is often difficult to determine whether bacteria detected in middle ear fluid specimens originated from the middle ear or the external auditory canal. Recent in vitro studies suggest that bacterial interactions in the nasal/nasopharyngeal microbiome may affect otitis media pathogenesis by modifying otopathogen behaviours. Impacts of environmental pressures (e.g. smoke, nutrition) and clinical interventions (e.g. vaccination, antibiotics) on the upper respiratory and middle ear microbiomes remain poorly understood as there are few data. Implications for practice: Advances in understanding bacterial dynamics in the upper airway microbiome are driving development of microbiota-modifying therapies to prevent or treat disease (e.g. probiotics). Further advances in otitis media microbiomics will likely require technological improvements that overcome the current limitations of OMICs technologies when applied to low volume and low biomass specimens that potentially contain high numbers of host cells. Improved laboratory models are needed to elucidate mechanistic interactions among the upper respiratory and middle ear microbiomes. Minimum reporting standards are critically needed to improve inter-study comparisons and enable future meta-analyses.